Association between serum vitamin D levels and sensitivity to thyroid hormone indices: a cross-sectional observational study in NHANES 2007–2012 - Chen, Si; Yang, Wei; Guo, Zhen; Lv, Xiaofei; Zou, Yandun (Frontiers in Endocrinology, 2023)
Objective: We designed this study to determine whether there is a link between vitamin D levels and sensitivity to thyroid hormone and to provide a new perspective for studying the relationship between vitamin D and thyroid disease.Our study included 8,126 participators from the National Health and Nutrition Examination Survey (NHANES) database between 2007 and 2012. We used weighted multiple linear regression models to enquire the connection between serum vitamin D levels and thyroid hormone sensitivity indicators, including the following: Thyroid-stimulating hormone index (TSHI), Free Triiodothyronine/Free thyroxine (FT3/FT4), Thyroid Feedback Quantile-based Index (TFQI), and Thyrotroph Thyroxine Resistance Index (TT4RI). Finally, we used constrained cubic splines to explore possible nonlinear relationships. All data cleaning and statistical analyses were performed using R software.The final Results were reached after adjusting for various confounding factors. We found a U-shaped relationship between TFQI and serum vitamin D, and the lowest TFQI appeared when the serum vitamin D concentration was 25.77ng/ml. However, an inverse U-shaped relationship was found between FT3/FT4 and vitamin D levels. When the serum vitamin D concentration was 25.43ng/ml, the ratio of FT3/FT4 was the highest.In the US population, our study concluded that FTQI and FT3/FT4 were U-shaped or inverse-U-shaped with serum vitamin D levels respectively after several adjustments. Therefore, FTQI and FT3/FT4 are considered indicators of the complex relationship between thyroid hormone resistance and vitamin D metabolism. In the future, more complex prospective investigations are needed to confirm these findings and find a causal link between them.